Deep brain stimulation and suicide attempts in treatment-resistant patients: a case report and neuroethical analysis - D’Imperio, Ambra; Ienca, Marcello (Frontiers in Psychiatry, 2024)
This case presents the situation of a 66-year-old woman diagnosed with Multiple System Atrophy Parkinsonian Type who underwent deep brain stimulation (DBS) therapy and subsequently made two suicide attempts. Despite receiving treatment and extensive psychotherapy, her condition did not improve, leading to suicidal behavior over the course of a year. Notably, she held unrealistic beliefs about the effectiveness of DBS therapy, expressing dissatisfaction with its outcomes. Family dynamics were complex, with the patient concealing her psychological distress while coping with her worsening health condition. This severe distress culminated in two suicide attempts within a relatively short timeframe. Our psychiatric team promptly intervened, implementing a suicidality protocol and adjusting her medication regimen. Despite a documented prevalence of suicidal ideation and attempts post-DBS in the literature, the exact causes remain uncertain, with the suggested involvement of neuroimmune or neurological pathways. This case contributes to scientific understanding by shedding light on suicide attempts following ineffective DBS interventions, emphasizing the patient’s right to be informed about potential suicide risks and the possibility of assisted suicide through a neuroethical analysis. Therefore, our case underlines the importance of psychiatric evaluation and intervention in DBS patients to prevent further suicidality, focusing on a multidisciplinary approach tailored to the patient’s autonomy and neuroethical principles.